2010
DOI: 10.4314/jasem.v13i4.55387
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Heavy Metals Concentration in Abattoir Dumping Site Soil in Nigeria

Abstract: Assessment of seasonal variation in concentration of the heavy metals-Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn-in Abattoir dump site soil at Yauri, Nigeria, was undertaking during the two major seasons of Nigeria. This was done to determine the environmental pollution status of the soil at the dump site. Soil samples (0-15cm) collected during the 2007/2008 rainy and dry seasons were treated and digested using microwave acid digestion methods. The heavy metal concentrations were determined with Atomic Absorption spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
77
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 15 publications
18
77
14
1
Order By: Relevance
“…This result agrees with that of Yahaya et al (2009). Results recorded in this study have shown that the mean Cu concentration at Apir was higher than that obtained at North bank shops location.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This result agrees with that of Yahaya et al (2009). Results recorded in this study have shown that the mean Cu concentration at Apir was higher than that obtained at North bank shops location.…”
Section: Resultssupporting
confidence: 92%
“…These results conform to that of Yahaya et al (2009) who carried out a similar study in Nigeria. Tables 3 and 4 present the mean Pb content at Apir and North bank auto-mechanic shops refuse dumpsites soil respectively.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Bird species are usually exposure to cadmium through ingestion of food [8] from farmland where crops are cultivated in contaminated soils, atmospheric deposition, and water and from inhalation. When cadmium is present in soils it can be extremely dangerous, as the uptake through food will increase rapidly over time [9]. Birds are predominantly susceptible to the effects of anthropogenic activities in the environment and they have been recognized as good indictors of environmental contamination because of their abundance, wide distribution, feeding at different tropic levels, and their long life span [10][11][12].…”
Section: Introductionmentioning
confidence: 99%